Predictors of Mortality for Nursing Home-Acquired Pneumonia: A Systematic Review. - Dhawan, Naveen; Pandya, Naushira; Khalili, Michael; Bautista, Manuel; Duggal, Anurag; Bahl, Jaya; Gupta, Vineet (BioMed Research International, 2015)
Background. Current risk stratification tools, primarily used for CAP, are suboptimal in predicting nursing home acquired pneumonia (NHAP) outcome and mortality. We conducted a systematic review to evaluate current evidence on the usefulness of proposed predictors of NHAP mortality. Methods. PubMed (MEDLINE), EMBASE, and CINAHL databases were searched for articles published in English between January 1978 and January 2014. The literature search elicited a total of 666 references; 580 were excluded and 20 articles met the inclusion criteria for the final analysis. Results. More studies supported the Pneumonia Severity Index (PSI) as a superior predictor of NHAP severity. Fewer studies suggested CURB-65 and SOAR (especially for the need of ICU care) as useful predictors for NHAP mortality. There is weak evidence for biomarkers like C-reactive protein and copeptin as prognostic tools. Conclusion. The evidence supports the use of PSI as the best available indicator while CURB-65 may be an alternative prognostic indicator for NHAP mortality. Overall, due to the paucity of information, biomarkers may not be as effective in this role. Larger prospective studies are needed to establish the most effective predictor(s) or combination scheme to help clinicians in decision-making related to NHAP mortality.